Peran Perikatan dalam Menjamin Kepastian Hukum bagi Investor di Sektor Properti Indonesia - Alvin Nur Sulistiawan; Alya Caesar Nurohma; Arianto Gunadi (Program Studi Ilmu Hukum, Universitas Kuningan, 2024)
Agreements in the Indonesian property sector have an important role in ensuring legal certainty for investors. This engagement includes investment agreements, contracts, and other agreements that regulate the relationship between parties involved in the property business. In this engagement, it regulates the role of investors in the property business. This engagement is very important because it provides legal certainty for investors in guaranteeing their rights and avoiding conflicts that can arise in the property business. In addition, it also helps to resolve settlements that may arise in the property business in a fair and transparent manner. The research method used in this article is a case study with a qualitative approach with research using secondary data from several sources such as books, journals, articles, and related news. Thus in this research, it is found that the engagement in the Indonesian property sector has an important role in ensuring legal certainty for investors. This engagement helps ensure the rights and obligations of each party, so that the property business can run smoothly and safely.